Airborne olive pollen counts are not representative of exposure to the major olive allergen Ole e 1. Issue 6 (6th May 2013) - Galan, C.; Antunes, C.; Brandao, R.; Torres, C.; Garcia‐Mozo, H.; Caeiro, E.; Ferro, R.; Prank, M.; Sofiev, M.; Albertini, R.; Berger, U.; Cecchi, L.; et al.
Abstract Pollen is routinely monitored, but it is unknown whether pollen counts represent allergen exposure. We therefore simultaneously determined olive pollen and Ole e 1 in ambient air in Córdoba, Spain, and Évora, Portugal, using Hirst‐type traps for pollen and high‐volume cascade impactors for allergen. Pollen from different days released 12‐fold different amounts of Ole e 1 per pollen (both locations P < 0.001). Average allergen release from pollen (pollen potency) was much higher in Córdoba (3.9 pg Ole e 1/pollen) than in Évora (0.8 pg Ole e 1/pollen, P = 0.004). Indeed, yearly olive pollen counts in Córdoba were 2.4 times higher than in Évora, but Ole e 1 concentrations were 7.6 times higher. When modeling the origin of the pollen, >40% of Ole e 1 exposure in Évora was explained by high‐potency pollen originating from the south of Spain. Thus, olive pollen can vary substantially in allergen release, even though they are morphologically identical.